Pengaruh Corporate Social Responsibility dan Perencanaan Pajak terhadap Nilai Perusahaan - Rananda Septanta; Sapta Setia Darma; Muhamad Eko Ari Wibowo; Rijal Arslan (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The increasing demand for sustainable business practices and the growing attention to corporate fiscal strategies have made Corporate Social Responsibility (CSR) and Tax Planning central issues in evaluating firm performance, particularly in the agricultural manufacturing sector, which is closely associated with environmental and social impacts. This study aims to provide empirical evidence on the influence of CSR and Tax Planning on Company Value in agricultural-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period. This research uses a quantitative approach with an associative research design. The population consists of all agriculture companies listed on the IDX, from which 18 companies were selected through purposive sampling, resulting in 70 financial report observations. Data were processed using SPSS 25 and analyzed using multiple linear regression. Hypothesis testing was performed at a 5% significance level. The findings reveal that CSR does not have a significant effect on Company Value, indicating that CSR initiatives in this sector may not yet be perceived by investors as value-enhancing. Conversely, Tax Planning shows a significant positive effect on Company Value. Additionally, CSR and Tax Planning simultaneously exert a significant influence on Company Value. These results underscore the role of effective tax strategies in enhancing firm value within the agricultural manufacturing industry.